2021
DOI: 10.3390/met11122058
|View full text |Cite
|
Sign up to set email alerts
|

MQL-Assisted Hard Turning of AISI D2 Steel with Corn Oil: Analysis of Surface Roughness, Tool Wear, and Manufacturing Costs

Abstract: Precision hard turning (HT) gained more and more attention in the cutting industry in the last years due to continuous pressure of the global market for reducing costs, minimizing the environmental and health issues, and achieving a cleaner production. Therefore, dry cutting and minimal quantity lubrication (MQL) became widely used in manufacturing to meet the environmental issues with respect to harmful cutting fluids (CFs). Vegetable oils, in MQL machining, are a promising solutions to petroleum-based CFs; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Consequently, to improve the machinability of hardened steel during hard turning, the selection of appropriate experimental strategy, modeling and multi-objective optimization methodology is highly essential to select appropriate process parameters and their optimum range. Several investigations have been carried by applying different experimental design, 3133 modeling technique, 3436 and optimization methodology 3741 under environmentally sustainable cooling-lubrication systems 4246 with many cutting tool materials 4751 to enhance the cutting performance 5258 and machinability, 7,59,60 to predict the output value of different responses, and to optimize various cutting variables in HT of different workpiece materials (X210Cr12, 56 EN-24, 32,57 AISI 202, 55 AISI 304, 8,58 AISI 316, 45 AISI 420, 42 AISI 630, 24 AISI 1015, 53 AISI 1040, 13,39 AISI 1045, 15,33 AISI 1060, 7,37,38,43 AISI 2205, 26 AISI 4140, 14,34,41,50 AISI 4340, 2…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to improve the machinability of hardened steel during hard turning, the selection of appropriate experimental strategy, modeling and multi-objective optimization methodology is highly essential to select appropriate process parameters and their optimum range. Several investigations have been carried by applying different experimental design, 3133 modeling technique, 3436 and optimization methodology 3741 under environmentally sustainable cooling-lubrication systems 4246 with many cutting tool materials 4751 to enhance the cutting performance 5258 and machinability, 7,59,60 to predict the output value of different responses, and to optimize various cutting variables in HT of different workpiece materials (X210Cr12, 56 EN-24, 32,57 AISI 202, 55 AISI 304, 8,58 AISI 316, 45 AISI 420, 42 AISI 630, 24 AISI 1015, 53 AISI 1040, 13,39 AISI 1045, 15,33 AISI 1060, 7,37,38,43 AISI 2205, 26 AISI 4140, 14,34,41,50 AISI 4340, 2…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of green radiator coolant as a cutting fluid with MQL system unlocks several important domains. Nowadays, production industries are growing on a large scale, and both the State and central government are imposing strict regulations towards green and sustainable manufacturing policies [ 16 , 17 , 18 ]. That is why several scientists and researchers have been attempted on environmentally sustainable cooling-lubrication systems to enhance the cutting performance and machinability of different hard-to-cut and difficult-to-cut workpiece materials during turning operations (EN-24, EN-31,42CrMo4, 17CrNiMo6, Haynes-25, Ti6Al4V, Inconel 825, 800, 718, AISI 202, AISI 316, AISI 420, AISI 1015, AISI 4140, AISI 4340, AISI 1045, AISI 1060, AISI 52100, AISI D2, D3) [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dry and nearly dry machining is highly desirable as it is more sustainable than flood machining [3]. In many comparative research studies, MQL performed better than flood machining in surface quality, manufacturing cost, environmental impact, and tool life [3][4][5]. Careful cutting fluid selection is important due to its ecological and human health concerns [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oils are biodegradable and have no harmful effect on interaction with humans [6]. Arsene et al [5] concluded that, compared to petroleum-based cutting fluids, vegetable oil, i.e., pure corn oil, is more economical and environmentally friendly in MQL-assisted turning of hardened AIDI D2 steel. The study of Kuram et al [7] revealed that canola cutting fluid is better than sunflower and commercial semi-synthetic cutting fluid in multi-response optimization of surface roughness, tool life, and specific energy during the milling of stainless steel.…”
Section: Introductionmentioning
confidence: 99%